(untitled) (Journal of Research Updates in Polymer Science, 2019)
Poly Vinyl Alcohol (PVA) films were prepared using solution casting. The Tensile Strength (TS), Tensile Modulus (TM) and Elongation at break (Eb) of the prepared films were found to be 23.58 MPa, 32 MPa and 302% respectively. Moisture content and water uptake analysis were also checked. Then, gelatin and nano crystalline cellulose (NCC) were incorporated into PVA film and again physchio-mechanical properties were measured. The TS, TM and Eb values of PVA/Gelatin-based films were 23.57 MPa, 114.58 MPa, 48.10% respectively. On the other hand, PVA/Gelatin/NCC-based films showed the TS, TM, and Eb values of 32.92 MPa, 129.8 MPa, 58.5% respectively. Thermal degradation test was accomplished by Thermo-Gravimetric Analysis (TGA) and Differential Scanning Calorimetry (DSC). Spectroscopic analysis was also done by Fourier Transfer Infra-Red (FTIR). The soil degradation test confirmed the inherent biodegradable nature of the films. The prepared bio-polymeric films were exposed to gamma radiation. It was found that at 6 kGy dose the mechanical properties of the films improved significantly.